Reflex effects of laryngeal irritation on the pattern of breathing and total lung resistance - Boushey, H. A. (1972)
1. The reflex responses to chemical and mechanical irritation of the laryngeal mucosa have been studied by applying stimuli to the open larynx of tracheostomized cats while monitoring ventilatory and circulatory variables. The responses were studied before and after vagotomy and before and after denervation of the larynx by transection of the superior and recurrent laryngeal nerves. 2. The immediate response to laryngeal irritation was not consistent. The most frequent responses were coughing, and slowing and deepening of breathing without coughing. Less common were expiratory apnoea and sustained, simultaneous inspiratory and expiratory activity. 3. A consistent late change in the pattern of breathing occurred. Slower, deeper breathing with increased total lung resistance (bronchoconstriction) was seen after the immediate response abated. 4. The slowing of breathing was due to prolongation of both the time for inspiration and the time for expiration. The rate of increase in phrenic nerve activity was also slowed. 5. Vagotomy did not alter qualitatively the reflex changes in the pattern of breathing, although bronchoconstriction no longer occurred. 6. The responses were abolished by denervation of the larynx.